Plant cell lines in cell morphogenesis research - Seifertová, Daniela; Klíma, Petr; Pařezová, Markéta; Petrášek, Jan; Zažímalová, Eva; Opatrný, Zdeněk (Methods in molecular biology (Clifton, N.J.), 2014)
Plant organs and tissues consist of many various cell types, often in different phases of their development. Such complex structures do not allow direct studies on behavior of individual cells. In contrast, populations of in vitro-cultured plant cells represent valuable tool for studying processes on a single-cell level, including cell morphogenesis. Here we describe characteristics of well-established model tobacco and Arabidopsis cell lines and provide detailed protocol on their cultivation, characterization, and genetic transformation.
Keywords: Research; Mitosis; Cell Line; výzkum; mitóza; proliferace buněk; Arabidopsis; buněčné kultury; Cell Survival; Plant Cells; buněčné linie; Cell Culture Techniques; viabilita buněk; rostlinné buňky; vývoj rostlin; Plant Development; Cell Proliferation